Pengaruh Peer Group Education Terhadap Kualitas Hidup Dengan Hipertensi Di Posyandu Lansia Desa Sumberbendo Kecamatan Pare Kabupaten Kediri - Evi Cahayati; Nove Lestari (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2018)
The most frecuent health problems experienced by the elderly are hypertension, this can affect the quality of life of the elderly. Efforts to improve the quality of life of the elderly can be through Peer Group Education. Peer Group Education was the process of delivering education and information submitted to groups of people who feel they had some similarities in terms of age, mindset, interests or other things to people who claim or had something similar. The purpose of this research to determine the effect of peer group education on elderly life quality with hypertension. The research method was used Pre-Experimental Design with simple random sampling technique with a population of 24 people and a sample of 8 people in Elderly PosyanduSumberbendo villages. The measuring instrument was used for independent variables used SOP (operational standard of implementation) and for the dependent variable used quality of life questionnaire. The results of research on the effect of peer group education on the quality of life of elderly with hypertension obtained 100% before peer group education had the quality of life was and after done almost 50% had high quality of life. Based on the Wilcoxon Signed Ranks Test to determine the effect of Peer Group Education on Elderly Life Quality With Hypertension obtained p-value of 0.046 α = 0.05 then p-value <α so it was concluded that H1 accepted or it can be said Peer Group Education can affect the Quality of Elderly Life with Hypertension in Elderly Posyandu Sumberbendo Villages Pare District Kediri Regency. It was expected that every elderly Posyandu can activate Peer Group Education activities as a forum for discussion and increase information and to improve the quality of life of the elderly.